2008
DOI: 10.3746/jkfn.2008.37.5.542
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Glucose-regulating Enzymes and Antioxidant Activities of Water Extracts from Medicinal Herbs

Abstract: This study investigated the anti‐diabetic effects of water extracts from Korea medicinal herbs on hepatic glucose‐regulating enzymes, such as acetyl‐CoA carboxylase (ACC) and glucokinase (GK). The hepatic cytosol faction of a type ? diabetic animal (GK rat, Goto‐kakizaki) was used in acetyl‐CoA carboxylase (ACC) and glucokinase (GK) activity assays. Type 2 diabetes generally characterized by non‐insulin‐dependent hyperglycemia in early stages and the therapeutic approach available is by retarding absorption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The butanol fraction of AC has been shown to reduce blood glucose levels, plasma triglycerides, free fatty acids, and cholesterol in streptozotocin-induced diabetic rats (Kim, 2003). Antioxidant and antidiabetic activities were also reported in rats (Choe et al, 2008). In addition, the butanol fraction of AC reduced peroxidative liver damage in streptozotocin-induced diabetic rats (Choi, 2004).…”
mentioning
confidence: 94%
“…The butanol fraction of AC has been shown to reduce blood glucose levels, plasma triglycerides, free fatty acids, and cholesterol in streptozotocin-induced diabetic rats (Kim, 2003). Antioxidant and antidiabetic activities were also reported in rats (Choe et al, 2008). In addition, the butanol fraction of AC reduced peroxidative liver damage in streptozotocin-induced diabetic rats (Choi, 2004).…”
mentioning
confidence: 94%
“…Two grams of freeze-dried black jujube was placed in a 50 mL falcon tube and extracted for 30 min with 18 mL of distilled water or 70% ethanol. The α-glucosidase inhibitory assay of the BJE was determined using a modified procedure reported by Choe et al ( 20 ). α-Glucosidase (EC 3.2.1.20) isolated from Saccharimyces cerevisiae and the substrate 4-nitrophenyl-α-D-glucopyranoside were purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it has been used to treat diabetes, pulmonary tuberculosis, disinfection, antidote, neuralgia and rheumatism (6). Pharmacological studies have revealed that it can act as an anti-oxidant, help regulate glucose levels (7)(8)(9) and act as an anti-cancer agent (10). In addition, it has been shown to have beneficial effects on obesity (11), immuno-regulation (12,13), intestinal function (14,15), and lipid metabolism (16).…”
Section: Introductionmentioning
confidence: 99%